2015
DOI: 10.9738/intsurg-d-14-00225.1
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lidocaine for Effective Pain Relief After a Laparoscopic Colectomy: A Prospective, Randomized, Double-Blind, Placebo-Controlled Study

Abstract: A perioperative intravenous lidocaine infusion has been reported to decrease postoperative pain. The goal of this study was to evaluate the effectiveness of intravenous lidocaine in reducing postoperative pain for laparoscopic colectomy patients. Fifty-five patients scheduled for an elective laparoscopic colectomy were randomly assigned to 2 groups. Group L received an intravenous bolus injection of lidocaine 1.5 mg/kg before intubation, followed by 2 mg/kg/h continuous infusion during the operation. Group C r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 24 publications
2
50
0
3
Order By: Relevance
“…After reviewing the full text, 15 additional irrelevant trials were excluded. Finally, the articles considered to be suitable for this meta‐analysis consisted of 10 RCTs, enrolling a total of 527 adult patients. The search process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reviewing the full text, 15 additional irrelevant trials were excluded. Finally, the articles considered to be suitable for this meta‐analysis consisted of 10 RCTs, enrolling a total of 527 adult patients. The search process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 studies, 2 studies were from Belgium; 2 studies were from Korea; 2 studies were from China; and the each of the remaining 4 studies were from France, Egypt, Lithuania, and Slovenia. All studies received IV lidocaine infusion before skin incision; five studies received IV lidocaine for more than 24 hours after surgery, and the other five studies infused lidocaine less than 24 hours after surgery. Most of the loading dose of lidocaine was 1.0 to 2.0 mg/kg, and continuous dose was 1.0 to 2.0 mg/kg/h.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the response of lymphocyte proliferation to phytohemagglutinin-M was improved, indicating that lidocaine attenuates surgery-induced immunosuppression. While Kaba et al 145 reported that concentrations of C reactive protein (CRP) were similar in both lidocaine and control groups in patients undergoing laparoscopic colectomies, Ahn et al 146 found that in the lidocaine group the plasma concentrations of CRP were decreased in patients undergoing the same procedure within the first two postoperative days 146…”
Section: Perioperative Analgesicsmentioning
confidence: 99%
“…Considering the pharmacological effects of IV lidocaine, which has both anti-inflammatory and analgesic effects (protein receptor inhibitor G and NMDA), lidocaine has been used to relieve postoperative pain [4]. According to numerous studies on various surgical procedures, intraoperative IV lidocaine infusion has been shown to reduce postoperative pain and nausea and vomiting [5][6][7][8][9][10][11][12][13][14]. Although the exact dosage is still unknown, the conducted studies have used 1-2 mg/kg/h dosages.…”
Section: Introductionmentioning
confidence: 99%